2010
DOI: 10.1530/rep-10-0047
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor-A isoform and (co)receptor expression are differentially regulated by 17β-oestradiol in the ovariectomised mouse uterus

Abstract: The angiogenic effects of 17b-oestradiol (E 2 ) in the mouse endometrium are mediated by vascular endothelial growth factor-A (VEGFA). We analysed the temporal and spatial changes in VEGFA isoform and (co)receptor expression in ovariectomised mouse uteri following E 2 treatment. VEGFA isoform and receptor mRNA were quantified in whole uterine tissue collected 2, 6, 12 and 24 h after E 2 or vehicle treatment. Laser capture microdissection was used to investigate mRNA expression in epithelial, stromal and myomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
1
12
1
Order By: Relevance
“…It is interesting that NRP2 expression was associated with gender difference in our experiment, suggesting that NRP2 expression may be regulated by the sex hormones. Previous studies have demonstrated that NRP2 mRNA was decreased by estrogen in animal models (Walter et al 2010), which was consistent with our observation to some extent and may partially elucidate why male patients had higher NRP2 expression in our experiment. However, the underlying mechanisms of the correlation between NRP2 expression and sex hormone level is still misty.…”
Section: Discussionsupporting
confidence: 93%
“…It is interesting that NRP2 expression was associated with gender difference in our experiment, suggesting that NRP2 expression may be regulated by the sex hormones. Previous studies have demonstrated that NRP2 mRNA was decreased by estrogen in animal models (Walter et al 2010), which was consistent with our observation to some extent and may partially elucidate why male patients had higher NRP2 expression in our experiment. However, the underlying mechanisms of the correlation between NRP2 expression and sex hormone level is still misty.…”
Section: Discussionsupporting
confidence: 93%
“…Transgenic mice were slightly older because tghFST315 mice do not demonstrate mating behaviour until ,8 wks of age (Lin et al 2008). Following bilateral ovariectomy, mice were left for a minimum of 7 days to recover and to allow for endometrial regression, before one of two steroid hormone protocols commenced (Heryanto and Rogers 2002;Walter et al 2005Walter et al , 2010Girling et al 2007). Protocol 1 (short-term oestrogen, E): mice were given a single subcutaneous (s.c.) injection of oestradiol-17b (100 ng in 100 mL peanut oil; Sigma-Aldrich, St Louis, MO, USA) or vehicle (100 mL peanut oil) 8 days post-ovariectomy (n ¼ 7-9 per group).…”
Section: Study 1: Examination Of Fst Transgenic Oviducts and Uterimentioning
confidence: 99%
“…Estrogen regulates several angiogenic factors in the mouse uterus, including Angiopoietin-2 and VEGF (Walter et al 2010;Guo et al 2012). Furthermore, similar to human decidual cells (Gibson et al 2013), mouse decidual cells are able to synthesize estrogen during pregnancy, which is critical for endometrial angiogenesis.…”
Section: Discussionmentioning
confidence: 99%